Measurement of IL-10 levels in spleen tissue of experimentally immunosuppressive (BALB/ C) mice infected with Cryptosporidium spp. (Journal of the College of Basic Education, 2025)
Cryptosporidium spp. which can cause weight loss and severe watery diarrhea, is often found in the intestinal tracts of both animals and humans. However, little is known about the host immune responses elicited upon infection with Cryptosporidium spp. Although cryptosporidiosis due to Cryptosporidium spp. generally self-limiting in immunocompetent individuals, it can be lethal in immunocompromised or in immunosuppressed hosts, such as infants and HIV/AIDS. Current study aimed to investigate of IL-10 Level in spleen homogenate for immunosuppressant BALB/ C mice by dexamethasone and infected with Cryptosporidium spp. Level of IL-10 appeared to increase in infected group (infected with Cryptosporidium spp.) (1446.93 ±161.02 pg/ml) compared to control group (non-infected) (641.20±40.42pg/ml), while it get decreased in immuno suppressant group (immuno suppressed by dexamethasone and infected with Cryptosporidium spp.) (872.26 ±46.20 pg/ml) P≤0.001. The results of the current study may provide benefit to future research on the immune response to Cryptosporidium spp. infection in temporary immunosuppressed populations.